2008
DOI: 10.1002/jcp.21566
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of retinal neovascularization by gene transfer of small interfering RNA targeting HIF‐1α and VEGF

Abstract: Retinal neovascularization (NV) occurs in various ocular disorders including proliferative diabetic retinopathy, retinopathy of prematurity and secondary neovascular glaucoma, which often result in blindness. Vascular endothelial growth factor (VEGF) is an essential growth factor for angiogenesis, and is particularly regulated by hypoxia inducible factor-1alpha (HIF-1alpha) under hypoxic conditions. Therefore, HIF-1alpha and VEGF could provide targets for therapeutic intervention on retinal NV. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…It has been reported that the silencing of HIF-1α is effective at inhibiting retinal neovascularization in experimental mice models (Jiang et al, 2009).…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…It has been reported that the silencing of HIF-1α is effective at inhibiting retinal neovascularization in experimental mice models (Jiang et al, 2009).…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…OIR mice were anesthetized intraperitoneally with 1% pentobarbital sodium (30 mg/kg body weight) and given an intravitreal injection of recombinant PGC-1α or PBS. The tip of a 10 mm 34-gauge steel needle, mounted on a 5 µl Hamilton syringe, was pushed through the sclera, 1 mm posterior to the corneoscleral limbus, into the vitreous body (18). OIR mice received an intravitreal injection of 1 µl (0.25 µg/µl) recombinant PGC-1α (OIR PGC-1α group) or 1 µl PBS (OIR control group) at P11, and were returned to room air at P12.…”
Section: Measurement Of Vegf Protein Expression In Hrvecs Usingmentioning
confidence: 99%
“…The silencing of hypoxia inducible factor-1alpha (HIF-1alpha), that regulates the VEGF expression in hypoxic conditions of ocular angiogenesis is also under investigation to treat CNV (93). siRNA targeting the TGF-β, involved in fibrotic scars, seems to be another great potential to treat AMD (94).…”
Section: Small Interference Rna (Sirna)mentioning
confidence: 99%